Internalization of Islamic Educational Values through the Merariq - Mukminah Mukminah; Hirlan Hirlan (Journal La Edusci, 2026)
The marriage tradition of the Sasak Merariq is ideally a vehicle for Islamic character education, based on the philosophy of "Customs with the joint of Syara', Syara' with the joint of Kitabullah" (Customs are based on Islamic Law, Islamic Law is based on the Book of Allah). However, contemporary practices reveal a significant erosion of meaning due to modernization, pragmatism, and external stigma. This research aims to fill the literary gap, going beyond previous research that only describes the Merariq ritual or identifies its values, by deconstructing the psychological and sociological mechanisms of internalizing the value of Islamic education in it. Using a qualitative approach with a case study design in Central Lombok, this study collected data through in-depth interviews, participant observations, and documentation. Key findings reveal that the internalization of values does not occur through indoctrination but through risk-based pedagogy and social drama. Processions such as selarian (eloquence) and selabar (deliberation) function as a structured experiential learning curriculum where values such as syaja'ah (courage), amanah (responsibility), solidarity, and consultation are tested and lived in practice. The study also confirms the challenges posed by commercialization and the pressures of modernist and puritan views. As a solution, this study recommends revitalizing meaning through cultural literacy, expanding the role of key actors such as negotiators to cultural educators, thus transforming Merariq back into a functional and relevant medium for character education.